Subventricular zone cytoarchitecture changes in autism. - Kotagiri, P; Chance, SA; Szele, F; Esiri, M (2014)
Autism is thought to be a neurodevelopmental disorder with symptoms developing during neonatal neurogenesis in the subventricular zone (SVZ). Autism associated genes alter SVZ proliferation and cytoarchitecture, yet the response of the human SVZ in autism is unknown. Epilepsy drives neurogenesis in rodents, but it is unclear how epilepsy interacts with autism in SVZ responses. The striatal and septal SVZ derive from separate lineages in rodents and generate different interneuron types. Yet it is unclear if autism unevenly regulates the striatal and septal SVZ. The human SVZ was immunohistochemically examined post-mortem from individuals with autism (n = 11) and controls (n = 11). Autism showed a lower cell density in the septal, but not striatal, SVZ hypocellular gap only in the absence of epilepsy. There was a decline in septal hypocellular gap cells with age in autism, but no correlation with age in controls. In contrast, PCNA+ cell numbers increased only in autism with epilepsy both in the hypocellular gap and in the ependymal layer on the septal but not striatal side. Ependymal cells also became GFAP immunoreactive in autism irrespective of epilepsy co-morbidity; however, this only occurred on the striatal side. In examining these questions we also discovered a subset of ependymal, astrocyte ribbon and RMS cells which express PCNA and Ki67, PLP, and α-tubulin. These results are the first example of a neuropsychiatric disease differentially affecting the septal and striatal SVZ. Altered cell density in the hypocellular gap and proliferation marker expression suggest individuals with autism may follow a different growth-trajectory.